Інвестиційна привабливість України - Грицаєнко, Галина Іванівна; Грицаенко, Галина Ивановна; Hrytsaienko, Halyna; Грицаєнко, Микола Ігорович; Грицаенко, Николай Игоревич; Hrytsaienko, Mykola (Акад. екон. наук України, Ін-т екон. і соціал. наук Вроцлав. природ. ун-ту, Харк. нац. техн. ун-т сільс. господ. ім. Петра Василенка, 2017)
UA:У статті проаналізовано інвестиційну привабливість України порівняно з країнами – колишніми республіками СРСР. На підставі висновків міжнародних рейтингових агенцій стосовно місця в них України обґрунтовано шляхи покращення інвестиційної привабливості на основі боротьби з корупцією, судової та податкової реформ, валютного регулювання та розбудови банківського сектора. EN:The article is an analysis of investment attractiveness of Ukraine compared with countries – former Soviet republics – and study ways to improve it. Determining the investment climate based on an integrated approach to the interpretation of the essence in this category as a combination of various factors that characterize the advisability of investing in the country. Since independence, Ukraine, whose economy is the main macroeconomic indicators was the leader among the former Soviet republics, significantly lost its position worsened and investment attractiveness. Conclusions regarding international rating agencies place them in Ukraine give grounds to assert the possibility of using international experience, particularly in terms of reforms that promote positive development in the economy. We believe that the national model needs to improve the investment attractiveness of the real fight against corruption and judicial reforms to protect investors' rights in the courts, currency regulation and development of the banking sector, effective and comprehensive tax reform.
Investment attractiveness of Ukraine
Keywords: валовий продукт; бізнес; індекс BDO; інвестиційнa привабливость; інвестиції; index BDO; investment attractiveness; business